PENGARUH KOMPETENSI, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI UNIT PELAKSANA PELAYANAN TERPADU SATU PINTU (UP PTSP) KOTA ADMINISTRASI JAKARTA BARAT - Yulianto, Eka; Djati, S. Pantja (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
This study aims to examine and analyze the influence of competencies on employee performance, the effect of motivation on employee performance, the influence of organizational culture on the performance of employees of West Jakarta City Administrative One-Stop Services Unit and the simultaneous influence of competence, motivation and organizational culture on employee performance in West Jakarta City Administrative One-Stop Services. The sampling method used is simple random sampling. From a population of 210 Civil Servants, 138 people met the criteria of being sampled. The analytical method used in this study is multiple linear regression. The results of the study show that competency, motivation, and organizational culture together (simultaneous) significantly influence employee performance. Partially competence and motivation have a significant positive effect on employee performance, whereas organizational culture has a positive but not significant effect on employee performance. competence is the variable that has the greatest influence on employee performance.